2019
DOI: 10.28991/cej-2019-03091288
|View full text |Cite
|
Sign up to set email alerts
|

New Sintanyl Phosphonates for Protection of Oil and Gas Pipelines from Steel Corrosion

Abstract: Many corrosion inhibitors are economically disadvantageous or toxic to the environment. Additionally, there are certain requirements for corrosion inhibitors. Therefore, the development of new corrosion inhibitors is one of the important problems in the oil-producing and oil-refining industry. The purpose of this work is the synthesis of new corrosion inhibitors with high inhibitory activity, the establishment of the structure of the compounds obtained and the determination of the anti-corrosion effect with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several studies reported in the past decade on the corrosion inhibition of different types of steel in a CO 2 /H 2 S coexisting environment, [66–67,71a‐c,72,76,115,131d,140] as presented in Table 2. The solutions employed in these studies, consisting of either NaCl solutions [71–72,76,115,131d,140a] or brine and simulated oilfield waters, [66–67,140b,c] were usually saturated with both CO 2 and H 2 S. In a few of these studies, the authors also reported on the influence of either the pressure/concentration of CO 2 and H 2 S or their ratio on the corrosion inhibition of the respective CIs [66,72,76,115,140a] . In addition, Qiu et al [140b] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported in the past decade on the corrosion inhibition of different types of steel in a CO 2 /H 2 S coexisting environment, [66–67,71a‐c,72,76,115,131d,140] as presented in Table 2. The solutions employed in these studies, consisting of either NaCl solutions [71–72,76,115,131d,140a] or brine and simulated oilfield waters, [66–67,140b,c] were usually saturated with both CO 2 and H 2 S. In a few of these studies, the authors also reported on the influence of either the pressure/concentration of CO 2 and H 2 S or their ratio on the corrosion inhibition of the respective CIs [66,72,76,115,140a] . In addition, Qiu et al [140b] .…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…Nikitin et al [140c] . synthesized three new complexes of syntanyl‐ O ‐ethyl‐( N ‐morpholinyl) methylphosphonate and studied the impact of an increase in immersion time on the corrosion inhibition effectiveness of these complexes when employed as CIs for steel immersed in simulated oilfield water containing 250 g/m 3 CO 2 and 200 g/m 3 H 2 S. The authors concluded that for low immersion times (i. e. 6 h of immersion) the compounds with a lower degree of oxyethylation gave the highest corrosion inhibition effectiveness.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…In as-bought and normalised also there is a continuous reduction in the hardness values of the corresponding phases during spheroidisation. It is the indication of continuous stress relaxation and annihilation of crystal defects due to continuous isothermal soaking (Ismail et al, 2016;Nikitin et al, 2019;RSengupta et al, 2019;Suryo et al, 2018)…”
Section: Hardness Test Analysismentioning
confidence: 99%
“…Numerical detection of cavitation damage level and location on dam spillways is presented in [8]. Corrosion is another factor that determines the safety of pipelines, and the protection systems are essential against corrosion, especially for oil and gas pipelines [9].…”
Section: Introductionmentioning
confidence: 99%